Museum Hidup: Perkampungan Adat Nagari Sijunjung dalam Kancah Industri Pariwisata - Ermayanti Ermayanti; Edi Indrizal; Yevita Nurti; Ade Irwandi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The tourism sector is the main pillar of economic development in the context of the modernization era. So it can be said that tourism is an industry. The tourism industry that is being developed is based on culture. In the Nagari Sujunjung Indigenous Village, the development of a culture-based tourism industry can be seen through changing cultural elements such as the Rumah Gadang and Bakaua Adat rituals which are packaged in the form of a Matrilineal Festival by the government. This packaging is often referred to as commodification. With a qualitative method, the results show that the two cultures (tourism and local culture) become 'must' be modified to bridge and as a lubricant to respond to global challenges, so a dialogue will occur between the two. The dialogue is due to tourism having 'trace' and 'official' standards as well as culture having deep-rooted ideals. On the one hand, the noble cultural values of the community continue to be 'glorified' but on the other hand it is very interesting to be 'packaged'. However, local wisdom continues to be praised as a tradition that needs to be cared for and passed on, but its material and spiritual references are getting faded and messy. Apparently (in the era of globalization) it is not the tradition that needs to be defended, but the image of the tradition which is very easy to display (trade). On the other hand, efforts to commodify culture as a tourism industry are built on orientalist discourses, such as the living museum in the Nagari Sijujung Indigenous Village.